A New Multi-Rate Clock and Data Recovery Circuit - Guerrero, Erick; Sánchez-Azqueta, Carlos; Gimeno, Cecilia (Jornada de Jóvenes Investigadores del I3A, 2017)
A new bit rate adaptive clock and data recovery circuit able to operate in a range from 3.125 Mb/s to 2.5 Gb/s is presented in this work. It is designed in a standard CMOS technology, fed with a single supply voltage of 1.8 V and has a maximum power consumption of 140 mW.